Islamic studies and Islamic education in contemporary Southeast Asia - Kamaruzzaman Bustamam-Ahmad; Jory, Patrick (Yayasan Ilmuwan, 2011)
Seeking knowledge has long been a fundamental part of Southheast Asia's Islamic tradition. Traditionally, young muslims left their villages and even their homelands for the purpose of obtaining an education in Islam. Upon their return they were highly regarded in their community.